The influence of participation behavior (PB) and pro-environmental behavior (PEB) on environmental conservation (EC) among millennials in Langkawi / Muhammad Hafiz Azizan - Azizan, Muhammad Hafiz (2024)
The rapid growth of island tourism in Langkawi has brought significant impacts on the local inhabitants, their engagement behavior, socio-cultural settings, and the preservation of the island's natural heritage. While the development of local infrastructure and job opportunities can benefit the residents, it also poses potential negative effects on the environment, which in turn can impact the island's quality of life and tourist appeal. This study investigated the influence of awareness among Millennials in the host community on improving participatory behavior in environmental protection and conservation activities, as well as the development of sustainable island tourism. By examining the relationship between Participation behaviors (PB) and Pro-Environmental Behavior (PEB) on Environmental Conservation (EC) among Millennials, the study focused on understanding the effectiveness of pro-environmental behavior driven by awareness in fostering participatory behavior. The pivotal role of Millennials in ensuring the continuity of sustainable island tourism is emphasized. Quantitative method was employed to analyse data from three hundred ninety six respondents. Statistical Package for the Social Sciences (SPSS) and Partial Least Square-Structural Equation Modelling (PLS-SEM) were used in this study to investigate the associations between Millennials' involvement behavior and pro-environmental behavior. It likely involves estimating the structural model to test the hypothesised correlations and building a measurement model to evaluate the validity and reliability of the measurement scales utilised. In order to analyse the data and test the study hypotheses, these quantitative approaches offer a methodical and statistical approach, enabling researchers to make judgements based on empirical evidence. The study examined Millennials' involvement in environmental protection. Through numerous chapters, significant influencing variables for conservation were discovered. In relation to participation behavior, pro-environmental behavior, and environmental conservation, study objectives, a theoretical framework, and hypotheses were constructed. The results showed the importance of how to encourage self-awareness and environmentally responsible behavior among Millennials for sustainable practises. The research contributed to empirical evidence on the relationship between PB, PEB, and EC among Millennials in Langkawi, providing practical implications for policymakers, environmental organizations, and community leaders. The study underlined the role of Millennials in environmental conservation activities and offered insights into improving their participation through targeted interventions. It investigated the effect of residents' place image and connection on their pro-tourism behavioral intention. This includes how these characteristics influence their motivation to engage and support tourism-related environmental conservation initiatives, with assistance from Social Exchange Theory (SET) as the fundamental underpinning theory and the Theory of Planned Behavior (TPB). Moreover, this study supported the groundwork for future research on implementing strategies for sustainable island tourism.